Transparency Animations: Trusted Research Environments, Data Linkage and Synthetic Data - Coulson, Adam; Madden, Vicki (International Journal of Population Data Science, 2024)
Background With funding from HDR UK, Research Data Scotland (RDS) commissioned award-winning production company Media Co-op to create three short graphic animations targeted at both researchers and members of the public, building on our existing text-based content by introducing educational resources in a new format. These videos highlight three topics that have generated substantial interest among RDS users: Trusted Research Environments, data linkage and synthetic data. Introduction Founded in 2021, RDS’s brand values centre on providing clarity, encouraging simplicity and building public trust. These values closely align with the aims of the HDR UK Transparency Standards, particularly around transparent application processes and criteria (Standard 2) and consideration for target audiences (Standard 4). Methods RDS worked with creative agency Media Co-op to develop the animations with input from both subject matter experts and members of the public. Data experts were consulted throughout the project to ensure information accuracy. Two rounds of feedback from the Scotland Talks Data public panel, run jointly by RDS and the Scottish Centre for Administrative Data Research (SCADR), were also incorporated with the aim of ensuring appropriate and accessible language. Results The resulting animations explain complex topics in layperson terms to aid comprehension. Each video also has a corresponding British Sign Language (BSL) version to aid wider accessibility. We anticipate that these videos will ensure both researchers and the public can glean a clearer understanding of these intricate concepts. Conclusions By applying a Creative Commons Non-Commercial Share Alike 4.0 license to all three videos, we intend for all partner organisations across the UK to be able to reuse or share these videos with their respective audiences. The more organisations share these videos, the more we will build a collective understanding of these complex topics. The final animations can be viewed on the RDS YouTube channel: How is data kept secure? What is data linkage? What is synthetic data? To honour our commitment to creating accessible content, BSL versions of all three animations are also available: How is data kept secure? (BSL) What is data linkage? (BSL) What is synthetic data? (BSL)